Olorinab (APD371), a peripherally acting, highly selective, full agonist of the cannabinoid receptor 2, reduces colitis-induced acute and chronic visceral hypersensitivity in rodents. Issue 1 (January 2022) - Castro, Joel; Garcia-Caraballo, Sonia; Maddern, Jessica; Schober, Gudrun; Lumsden, Amanda; Harrington, Andrea; Schmiel, Shirdi; Lindstrom, Beatriz; Adams, John; Brierley, Stuart M.
Abstract : Abstract: Abdominal pain is a key symptom of inflammatory bowel disease and irritable bowel syndrome, for which there are inadequate therapeutic options. We tested whether olorinab—a highly selective, full agonist of the cannabinoid receptor 2 (CB2 )—reduced visceral hypersensitivity in models of colitis and chronic visceral hypersensitivity (CVH). In rodents, colitis was induced by intrarectal administration of nitrobenzene sulfonic acid derivatives. Control or colitis animals were administered vehicle or olorinab (3 or 30 mg/kg) twice daily by oral gavage for 5 days, starting 1 day before colitis induction. Chronic visceral hypersensitivity mice were administered olorinab (1, 3, 10, or 30 mg/kg) twice daily by oral gavage for 5 days, starting 24 days after colitis induction. Visceral mechanosensitivity was assessed in vivo by quantifying visceromotor responses (VMRs) to colorectal distension. Ex vivo afferent recordings determined colonic nociceptor firing evoked by mechanical stimuli. Colitis and CVH animals displayed significantly elevated VMRs to colorectal distension and colonic nociceptor hypersensitivity. Olorinab treatment significantly reduced VMRs to control levels in colitis and CVH animals. In addition, olorinab reduced nociceptor hypersensitivity in colitis and CVH states in a concentration- and CB2 -dependent manner. By contrast, olorinab did not alter VMRs nor nociceptor responsiveness in control animals. Cannabinoid receptor 2 mRNA was detected in colonic tissue, particularly within epithelial cells, and dorsal root ganglia, with no significant differences between healthy, colitis, and CVH states. These results demonstrate that olorinab reduces visceral hypersensitivity through CB2 agonism in animal models, suggesting that olorinab may provide a novel therapy for inflammatory bowel disease– and irritable bowel syndrome–associated abdominal pain. Abstract : Olorinab—a highly selective, full agonist of the cannabinoid receptor 2—significantly reduces visceral hypersensitivity and colonic nociceptor firing in inflammatory bowel disease–like and irritable bowel syndrome–like rodent models.